The Effect of Motor Games On Decreasing Anxiety - Abedulwahed, Ameer (Journal of Physical Education, 2016)
Game and playing are considered on the means that adults use to teach children how to express themselves and their abilities. The aim of the research was to identify anxiety in children aged 4 – 5 years old as well as designing a set of motor games to decrease anxiety in children and to identify the effect of these games on children's anxiety. The researcher hypothesized significant statistical differences between pre and posttests in the level of anxiety. The researchers used the experimental method; the subjects were preschoolers aged 4 – 5 years old from Al Besma and Al Gophran Preschools. The data was collected and treated using proper statistical operations to come up with the results. The researchers concluded that the program designed by the ministry of education as well as the program designed by the researchers have positive effects on decreasing anxiety in children aged 4 – 5 years old. The results showed significant differences between posttest in favor of the experimental group. Finally the researcher recommended the necessity of including variable motor games and conducting anxiety tests on children as well as making similar studies on other variables.